PENGARUH KARAKTERISTIK INDIVIDU DAN REWARD TERHADAP KINERJA KARYAWAN PADA PT. SERTIFIKASI SISTEM MANAJEMEN INDO RAYA DI KABUPATEN GIANYAR - Ni Made Juliantari; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee performance is one of the factors that determine the success of achieving organizational goals. The success of achieving these goals is determined by various factors, including individual characteristics and rewards. Individual characteristics and rewards are one of the factors that can affect employee performance so that they need to be consistently improved. The population in this study were 35 people. The sampling technique used is a saturated sample so that the entire population in this study is used as a sample of 35 respondents. Analysis of the data in this study using Multiple Linear Regression Analysis using the IBM SPSS Statistic 25 application. The results showed that individual characteristics and rewards had a positive and significant effect on employee performance at PT. Indo Raya Management System Certification in Gianyar Regency.